The Dynamics of forest Cover of India Based on Assessments Done by Forest Survey of India from 1987 to 2015 - Suyal, B. D. (Indian Forester, 2017)
The paper presented an analytical overview of the forest cover changes in the country since 1987 based on published reports of Forest Survey of India for clear appreciation of status of forest cover changes in the country. The first national perspective of Forest cover based on remote sensing data pertaining to 1981-83 was published in 1987 which estimated FC at 19.52% of the GA. That served as first bench mark at the National /State level. The methodology, quality of data, scale of mapping and interpretation techniques, since than, has improved gradually, some changes particularly in 1989, 2001 and 2009 have been quite significant. Technological advancement rendered the forest cover data of previous assessments incompatible. Thus, comparing the original time series of FC overlooking the change in technology/methodology might lead to inconsistent inferences. The complete data series beginning from 1987 was revised in 2009 by applying corrections on account of change in scale, capture of small patches and impact of polygon centric approach to overcome to a considerable extent the constraint of incompatibility. The technology and interpretation technique from 2009 to 2015 assessments remained largely unchanged. The analysis of revised data brought out that the FC increased in 2nd cycle then decreased gradually (except minor increase in 1993) till 1997. From 6th cycle, FC showed improvement (barring slight decline in 2011) till 14th cycle. The overall increase in FC in the country (between 1st to 14th cycle) was estimated as 60854 Km2 i.e. 1.85% of GA of the country. The FC grew annually by 194540 ha from 1984 to 1993, 264940 ha from 1994 to 2003 and 149060 ha from 2004 to 2013. Overall average annual growth of forest cover was estimated as 202847 ha for the entire period. The distribution of forest cover declined drastically with increase in altitude. Areas above 2000 m altitude contained only 8.39% of the total forest cover. More than half of the forest cover (52.47%) was contributed by areas below 500 m altitude. Analysis of digitized forest boundaries of 12 States/UT brought out that 73.15% (86.95% VDF, 78% MDF and 64.56 % OF) of forest cover was contributed by recorded forest areas and 26.85% (13.05% VDF, 22% MDF and 35.44% OF) by outside areas.